ANALISIS PENGARUH GAYA KEPEMIMPINAN, KOMPETENSI DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BANK OCBC NISP, TBK - Parmin, Yohanes (Management Research and Business Journal, 2023)
ABSTRACT This study aims to determine: (1) the effect of leadership style on the work performance of PT. Bank OCBC NISP, Tbk (2) The effect of competence on the work performance of employees of PT. Bank OCBC NISP, Tbk (3) Effect of job training on work performance of PT. Bank OCBC NISP, Tbk. The population and sample are 58 respondents. Using qualitative research methods with multiple linear regression analysis to determine the effect of leadership style (X1), competence (X2), job training (X3) and employee performance (Y). From the results of the research that has been done, multiple linear regression analysis is obtained as follows Y = 7.388 + 0.255X1 + 0.269X2 + 0.290X3. The t-test results of leadership style (X1) obtained t count (2.512) > t table (2.005) then Ho was rejected and H1 was accepted which means it affects employee performance, competence (X2) obtained t count (2.067) > t table (2.005 ) then Ho is rejected and H2 is accepted, which means it affects employee performance, job training (X3) is obtained by t count (2.766) > t table (2.005) then Ho is rejected and H3 is accepted, which means it affects employee performance. The results of the F test obtained an F table value of 2.78 where F count > F table (96.446 > 2.78) with a significance value of 0.000 <0.05 it can be concluded that H0 is rejected and H4 is accepted meaning leadership style (X1), competence ( X2), and job training (X3) together have a significant effect on employee performance (Y). The coefficient of determination (R2) is 0.817 or 81.7%, meaning that the influence of leadership style, competence and job training on employee performance is 81.7%. While the remaining 18.3% is explained by other variables that are not included in the problems of this study.